Effect of culture technique of Ganoderma australe mycelia on percentage removal of leachate organics / Wan Razarinah Wan Abdul Razak, Noor Zalina Mahmood and Noorlidah Abdullah - Wan Abdul Razak, Wan Razarinah; Mahmood, Noor Zalina; Abdullah, Noorlidah (Penerbit UiTM (UiTM Press), 2016)
Leachate (liquid pollutant), which is highly contaminated with organic matter and toxic substances is a major problem that arised from landfill. Biological methods have proven to be effective to remove organic matters that are abundant in leachate. This study is intended to compare the used of free mycelia and immobilized mycelia of the white-rot fungi, Ganoderma australe for the removal of landfill leachate organics. The organics fraction of landfill leachate was measured by biological oxygen demand (BOD₅), and chemical oxygen demand (COD). The experiment revealed that free mycelia of G. australe showed capability in removing leachate BOD₅ but not COD. However, the use of immobilized G. australe displayed the best result in the removal of BOD₅ and COD leachate after 4 weeks of treatment in flasks with 93.09% and 17.84% percentage removal of BOD5 and COD, respectively. Therefore, G. australe can be considered potentially useful in the treatment of landfill leachate as they can help in removing BOD and COD due to their biodegradative abilities.